Effects of Perfluorooctanoic Acid on the Associated Genes Expression of Autophagy Signaling Pathway of Carassius auratus Lymphocytes in vitro - Tang, Juan; Lu, Xiangjun; Chen, Feifei; Ye, Xueping; Zhou, Dongren; Yuan, Julin; He, Jianbo; Chen, Bin; Shan, Xiaodong; Jiang, Jinxiao; Liu, Wenli; Zhang, Hangjun (Frontiers in Physiology, 2018)
Perfluorooctanoic acid (PFOA) has been detected in various water bodies and caused harm to aquatic organisms. The aim of this study was to investigate the cytotoxicity and mechanism associated with autophagy and oxidative stress after exposure to PFOA (0, 1, 10, 100 µg/L) for 12 h on lymphocytes which was isolated from the head kidney of Carassius auratus (C. auratus). Both of autophagy formation, cell activity, and intracellular ROS, MDA, GSH and SOD levels were measured. The relative expression of partial autophagy-related genes autophagy related 5 (Atg 5), autophagy related 7 (Atg 7), and Beclin 1 were also cloned and detected. Homologous relationships analysis showed high identities of genes in C. auratus and other fish by blast. Fish lymphocytesgrowth inhibition rates was increased induced by PFOA. Compared with the control group, the reactive oxygen species (ROS) generation and the malondialdehyde (MDA) content were significantly increased in all of the PFOA-treated group. Besides, decreased superoxide dismutase (SOD) activity and decrease of glutathione (GSH) activity induced by PFOA further confirmed the occurrence of oxidative stress. The number of autophagosome formations was increased in a dose-dependent manner. Atg 7 and Beclin 1 mRNA expression was elevated significantly after PFOA exposed, showing a time-dependent manner, while expression of Atg 5 mRNA was increased remarkably in 100 µg/L PFOA treatment group compared with the contronl group. These results indicated that PFOA caused oxidative damage to lymphocytes in C. auratus and caused various autophagy signaling pathway-associated genes imbalances in the lymphocytes. Autophagy signaling pathway-associated genes imbalance could weaken antioxidant capacity and involve in the mechanism of C. auratus lymphocytes oxidative damage caused by PFOA.